A weak allele of OsNRAMP5 confers moderate cadmium uptake while avoiding manganese deficiency in rice. (5th July 2022) - Kuramata, Masato; Abe, Tadashi; Tanikawa, Hachidai; Sugimoto, Kazuhiko; Ishikawa, Satoru
Abstract : Substitution of Q337 in OsNRAMP5 shows that it is an important residue involved in metal transport and can be used to decrease Cd uptake in rice while avoiding Mn deficiency. Abstract: Decreasing cadmium (Cd) concentrations in rice grains can effectively reduce potential risks to human health because rice is the major contributor to Cd intake in many diets. Among several genes involved in rice Cd accumulation, the loss of function of OsNRAMP5 is known to be effective in reducing grain concentration by inhibiting root uptake. However, disruption of this gene simultaneously decreases manganese (Mn) uptake because OsNRAMP5 is a major Mn transporter. With the aim of improving Mn uptake in OsNRAMP5 mutants while still restricting the grain Cd concentration below the upper limit of international standards, we identified a novel OsNRAMP5 allele encoding a protein in which glutamine (Q) at position 337 was replaced by lysine (K). The mutant carrying the OsNRAMP5-Q337K allele showed intermediate Cd and Mn accumulation between that of the wild-type and OsNRAMP5- knockout lines, and exhibited more resistance to Mn deficiency than the knockout lines. Different amino acid substitutions at position Q337 significantly affected the Cd and Mn transport activity in yeast cells, indicating that it is one of the crucial sites for OsNRAMP5 function. Our results suggest that the OsNRAMP5-Q337K allele might be useful for reducing grain Cd concentrations without causing severe Mn deficiency in rice cultivars through DNA marker-assisted breeding.